2020
DOI: 10.3390/catal10020217
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution, Gene Expression Profile, and Secretion of Digestive Peptidases in Lepidoptera Species

Abstract: Serine peptidases (SPs) are responsible for most primary protein digestion in Lepidoptera species. An expansion of the number of genes encoding trypsin and chymotrypsin enzymes and the ability to upregulate the expression of some of these genes in response to peptidase inhibitor (PI) ingestion have been associated with the adaptation of Noctuidae moths to herbivory. To investigate whether these gene family expansion events are common to other Lepidoptera groups, we searched for all genes encoding putative tryp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Similar to that observed here for the Bt maize-resistant S. frugiperda population, Helicoverpa armigera (Hübner, [1808]) (Lepidoptera: Noctuidae) presented reduced growth and survival rates when ingesting an artificial diet containing Cry1Ac combined with a trypsin inhibitor ( Lomate and Hivrale 2013 ). Trypsins are key proteases involved in Lepidopteran larval digestion, having a significant role in primary digestion of proteins ( Srinivasan et al 2006 , Lima et al 2020 ). Blocking trypsin activity using trypsin inhibitors, such as SBTI, may result in negative effects on amino acid nutrition and, consequently, in insect development ( Macedo et al 2010 , Macedo and Freire 2011 , Zhu-Salzman and Zeng 2015 , Meriño-Cabrera et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to that observed here for the Bt maize-resistant S. frugiperda population, Helicoverpa armigera (Hübner, [1808]) (Lepidoptera: Noctuidae) presented reduced growth and survival rates when ingesting an artificial diet containing Cry1Ac combined with a trypsin inhibitor ( Lomate and Hivrale 2013 ). Trypsins are key proteases involved in Lepidopteran larval digestion, having a significant role in primary digestion of proteins ( Srinivasan et al 2006 , Lima et al 2020 ). Blocking trypsin activity using trypsin inhibitors, such as SBTI, may result in negative effects on amino acid nutrition and, consequently, in insect development ( Macedo et al 2010 , Macedo and Freire 2011 , Zhu-Salzman and Zeng 2015 , Meriño-Cabrera et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…But what appears to be a fact is that the great diversity of isoforms is important not only to deal with the diverse content of plant proteins but also to circumvent an expressive part of the PI‐based plant defense. Lima et al (2020) reported that approximately one‐third of the proteases expressed in the intestine of insects of the order Lepidoptera correspond to serine proteases (EC 3.4.16 and EC 3.4.21). This fraction of enzymes can represent up to 95% of the proteolytic activity in the larval intestine in lepidopteran (Srinivasan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Serine peptidase genes present in the H. armigera genome were identified using the BLASTP program with a set of well-described SP genes as the query [5]. The identified sequences were then filtered using the presence of a predicted trypsin domain (IPR001254) according to an InterproScan analysis and a complete catalytic triad (His57, Asp102, and Ser195) [61]. Subsequently, trypsin and chymotrypsin genes were classified according to the amino acid at position 189 (Asp for trypsin).…”
Section: Identification Of Serine Peptidase Gene Sequencesmentioning
confidence: 99%